English Syntax Learning; Student Errors in Analyzing Sentence Structure through Tree Diagrams - Marpaung, Fernando De Napoli; Donny Adiatmana Ginting; Muhammad Hassan; Rosmen; Yunita Sari Adelina (Institut Agama Islam Negeri Palopo, 2024)
This study aims to identify errors that are often made by 5th semester English language students in completing tree diagram assignments, especially in analyzing sentence structures in the Syntax course. The method used in this study is a descriptive qualitative approach, with data analysis techniques in the form of content analysis of 22 students who were divided into 10 groups to work on the task of making tree diagrams from English news texts from various sources. Based on the analysis, several types of main errors were found, namely errors in identifying word categories (168 words), incorrect node labeling (42 node labeling), and incorrect application of phrase structures (11 phrase structures). In addition, students also have difficulty in understanding the hierarchical relationship between syntactic elements, such as the correct placement of determiners and auxiliary verbs. These errors are often caused by a lack of understanding of basic word categories and the underlying syntactic rules. This study reveals that making tree diagrams requires a deep understanding not only of syntactic theory, but also its practical application in everyday sentence analysis. Errors in node labeling and errors in syntactic category identification indicate the need for a more contextual and deeper understanding-based learning approach.